Ultrasonic sensing using Yb3+/Er3+-codoped distributed feedback fibre grating lasers. - Ye, Chen-Chun; Tatam, Ralph P. (Institute of Physics (IOP), 2005)
Yb3+/Er3+-codoped distributed feedback (YbEr-DFB) fibre grating lasers have been investigated for the detection of ultrasonic Lamb waves generated in an aluminum plate. Two sensor configurations have been investigated. A path length imbalanced readout Mach- Zehnder interferometer was used to measure the laser frequency shift induced by ultrasonic vibration. The resolution to out-of-plane displacement was 3 x10-15 m/Ã Â Hz for a continuous ultrasonic wave at a frequency of 470 kHz. Ultrasonic waves were also detected by directly monitoring the laser output power. This simplified configuration is useful for tone burst AE signals generated by a low energy impact
Keywords: Ultrasonic sensing; distributed feedback fibre laser; fibre Bragg grating; Yb3+/Er3+-codoped fibre